PENGARUH METODE DISKUSI TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM: Studi Pada Sekolah Dasar Alam Anak Sholeh Tarumajaya Bekasi - Safitri, Heni; Nurrita, Teni (Asosiasi Dosen PTKIS Indonesia, 2024)
This research, the focus is: first, trying to find out how to apply the discussion method to the subject of Islamic Religious Education at Sekolah Alam Anak Sholeh Tarumajaya. Second, to find out how the learning outcomes of students in the Islamic Religious Education subject at Sekolah Alam Anak Sholeh Tarumajaya Bekasi. And third, to find out effective discussion methods and improve the learning outcomes of Islamic Religious Education at Sekolah Alam Anak Sholeh Tarumajaya Bekasi. This research was conducted using a descriptive method method with a quantitative approach. The population was 23 students with samples taken using the slovin margin error formula (5%), which was 22 students with sampling techniques, namely random sample sampling. Data collection uses observation methods and questionnaires which are processed using Rxy and analyzed through t-test (significant level). The importance of this research, where learning using the discussion method has a positive and significant influence on learning motivation, because with the discussion method, educators try to create an effective learning environment and involve all active studentsthrough interactions that occur in the classroom. With the formation of small groups, students can interact and exchange ideas with their group friends to obtain wider information. This discussion method is very appropriate in the subject of Islamic Religious Education at Sholeh Tarumajaya Children's Nature Elementary School.